Infestasi Cacing Usus dan Faktor-Faktor yang Mempengaruhinya pada Anak yang Tinggal di Daerah Aliran Sungai Siak Kelurahan Pesisir Kecamatan Lima Puluh Pekanbaru - Yolazenia Yolazenia; Suri Dwi Lesmana; Lilly Haslinda (Fakultas Kedokteran Universitas Riau, 2010)
Children living around river have higher risk to get helminthes infection. The aim of this study was to determine theprevalence and intensity of helminthes infection and its risk factors for children living around Siak River in KelurahanPesisir, Kecamatan Limapuluh, Pekanbaru. A cross-sectional study conducted in September to November 2008, and 65children participated. Stool were examined using the Kato-Katz technique and the intensity of infections was categorizedinto: light, moderate, or heavy. The parent of children was asked to fill the questionnaire. We found that 36,9%subjects were infected by intestinal helminthes. The most common infection was A.lumbricoides and T.trichiura. Mostof the subjects had light intensity of infection. There were no correlations between the habits of using river as: sourceof drinking water, place to defecate, place to take a bath and brush teeth, place to wash vegetables and kitchen tools,and the flood with helminthes infection.